Pembelajaran Fisika Berbasis Science Technology Engineering And Mathematics (Stem) Untuk Mengembangkan Keterampilan Kolaborasi - Cholis, Muhammad Ridwan Nur; Yulianti, Dwi (UPEJ Unnes Physics Education Journal, 2020)
In this 21st century, it is essential to teach some skills that are useful for the next generation, so they can compete with other countries. One of the skills that can be improved is collaboration skill. The teaching and learning process will run effectively if we use appropriate teaching method, that is STEM. STEM-based learning is a solution in helping to develop the 21st century (4C) learning skills through higher quality learning experiences. The results of observation at experiment school show that school have not applied to learn with the STEM approach and have not specifically developed collaboration skills. The purpose of this study was to determine the development of collaboration skills through the application of STEM-based physics learning. The research method used was a quasi-experiment with a nonequivalent control group design. The subjects of this study were students of class XI SMA Negeri 1 Kendal, class XI MIPA 3 as an experimental class, and XI MIPA 5 as an control class. Retrieval of data using observation and documentation methods. Analysis of research data using analysis of the observation sheet with the help of the SPSS and Microsoft Office Excel programs. The results showed that collaboration skills after applying STEM-based physics learning developed in the high category.